Therapeutic plasma exchange in neuro-immunological disorder - S., Aswin Kumar; B., Latha; Dhivya K., Dhivya x (International Journal of Research in Medical Sciences, 2017)
Background: Therapeutic plasma exchange (TPE) is an extracorporeal blood purification technique used to remove high molecular weight substances from the plasma. Examples of these substances include immune complexes, pathogenic autoantibodies, endotoxin, cryoglobulins and cholesterol-containing lipoproteins and myeloma light chains. Therapeutic Plasma exchange is a well-established therapeutic procedure most commonly used in many neuro-immunological disorders. The benefit of plasma exchange occurs by elimination of pathognomonic inflammatory mediators, including complement components, autoantibodies and cytokines. Various studied have demonstrated that TPE plays an important role in neuro-immunological disorder (eg. Guillain-Barré syndrome, myasthenia gravis and other forms of immune neuropathies). Methods: It is descriptive and prospective study on the effect of TPE in neuro-immunological disorders. TPE are studied prospectively for a period from September 2011 to August 2013. The amount of plasma to be exchanged during TPE was determined using the formula EPV = (0.065 x weight [kg]) x (1-hematocrit). TPE was performed using a Haemonetics MCS+ intermittent flow cell separator. An average of 1-1.5 plasma volume is removed on alternative days. Clinical outcome of TPE was assessed at the time of discharge. Results: A total of 138 Therapeutic plasma exchange procedure were performed on 30 patients. In which the improvement begins within days of commencing the treatments and progressed steadily so that 25 out of 30 patients who responded favourably to TPE with a manageable adverse reaction. And only 5 patients failed to respond this therapy. So the clinical outcome for therapeutic plasma exchange for Neuro-immunological cases were 83.3% and remaining 16.7% doesn’t show any improvement after five plasma exchanges. Conclusions: Therapeutic plasma exchange is a first line of management for most of the neuro-immunological disorder. In our study there was an improvement in motor performance after 3-5 plasma exchanges which are mainly due to removal of unbound antibodies from the plasma. Although the statistical power of our study was not sufficient to allow definitive conclusion, the result strongly suggest that 3-5 procedures on alternative days with 1-1.5 volume of plasma exchange gives a better result in patient with neuro-immunlogical diseases. The success of therapeutic plasma exchange also depends on composition of the replacement fluid. The risk and complication associated with procedure are also minimal and easily manageable.